Retarder effect on hydrating oil well cements investigated using in situ neutron/X-ray pair distribution function analysis. (December 2019) - Kupwade-Patil, Kunal; Boul, Peter J.; Rasner, Diana K.; Everett, S. Michelle; Proffen, Thomas; Page, Katharine; Ma, Dong; Olds, Daniel; Thaemlitz, Carl J.; Büyüköztürk, Oral
Abstract: Understanding the role of retarder on the chemical nature and molecular architecture of hydrating cement paste is essential for engineering oil well cements with additives. Here, synchrotron X-ray and total neutron scattering with pair distribution function (PDF) analysis were performed in combination with calorimetry and nuclear magnetic resonance (NMR) to examine the retarder effect in hydrating tri-calcium silicate (C3 S) and Class G oil well cement paste. Primarily, the retarder, Diethylenetriamine pentamethylene phosphonic acid (DTPMP) influenced the hydration by affecting the Ca-O and Ca-Si pair correlation providing evidence of calcium playing a predominant role in the retardation process. Secondary effects related to Calcium-Silicate-Hydrate (C-S-H) nuclei poisoning influencing the suppression of calcium hydroxide precipitation were observed. These findings provide insights into the retardation mechanism of hydrating cement paste influenced by calcium depletion when subjected to phosphonate retarders.